Streaming code across audiences and performers: An analysis of computer science communities of inquiry on Twitch.tv. (24th February 2022) - Gandolfi, Enrico; Ferdig, Richard E.; Clements, Robert
Abstract: Live streaming platforms like Twitch.tv count millions of viewers and performers, pointing to novel practices and interactions. Instructional applications of this phenomenon are rising with thematic channels and shows aimed at teaching and debating a variety of subjects ranging from art to programming. However, few research publications have specifically explored trends in pedagogical strategies and learning behaviours of viewing audiences. This study responded to this need by analysing computer science shows on Twitch.tv. A total of 40 hours of live streaming were analysed within a Community of Inquiry framework using the concepts of social affordances, computational thinking, and teaching style. Data collected from both expert and novice streamers included streamers' actions, on‐screen activity, and online discussions. Results pointed to specific tactics employed by both performers and viewers for exploring computer science issues and dynamics together, with instances of peer‐tutoring, construed learning, and significant transparency, even when top‐down instruction was staged. Practitioners notes What is already known about this topic Live streaming is a popular media practice all around the world, with Twitch.tv as the leading hosting platform. A rising number of live streaming shows are focusing on education and learning topics, from STEM to art. What this paper adds A first exploration of instructional streaming focused on computer science education. An analysis of best practices in instructional streaming in terms of community building, teaching style, and computational thinking processes. A better understanding of how communities of inquiry can be hosted on Twitch.tv. Implications for practice and/or policy Practitioners can harness this study's results for informing better educational streaming. Educators may refer to this article's highlights for selecting and evaluating educational streaming shows. Policy makers will be able to use this article's insights for monitoring and re‐applying effective computer science activities in other educational environments.